Cooperative learning and social cohesion: Study in the 4th year classes of tourism degree of Cuba and Mexico - Félix Díaz-Pompa; Nadia Vianney Hernández-Carreón; Idevis Lores-Leyva; Olga Lidia Ortiz-Pérez (Universidad de Deusto, 2023)
The comprehensive training of future professionals is a fundamental objective of Higher Education. In this sense, cooperative learning, while contributing to learning, also favors the development of social competences that promote the social cohesion of the group or class. The objective of this research is to compare two class groups of Bachelor's degree courses in Tourism from universities in Cuba and Mexico, taking into account the social cohesion achieved from the cooperative learning experience. The Social Network Analysis method is used to obtain those indicators that show the social cohesion achieved by these class groups subject to cooperative learning practices. The results show that the Cuban class group exhibits better results with respect to Mexico. On the other hand, some elements that should continue to be worked on from this experience for the development of social competencies and to achieve greater social cohesion are evidenced. Received: 8 April 2022 Accepted: 16 April 2023